The Heart's Frontier - Copeland, Lori; Smith, Virginia 1960- (Eugene, Or. : Harvest House Publishers, 2012)
When Emma Switzer's Amish family is robbed on a trip to visit relatives, leaving them destitute and stranded on the Kansas prairie, Luke Carson--a trail boss heading up his first cattle drive--is not Emma's first choice as an answer to her prayers.
Keywords: Amish -- Fiction -- Kansas; Cowhands -- Fiction; Kansas -- Fiction; Love stories; Christian fiction